Assertion and Certainty - Dinges, Alexander (Philosophical Quarterly, 2023)
Assertions have a curious relationship to certainty. On the one hand, it seems clear that we can assert many everyday propositions while not being absolutely certain about them. On the other hand, it seems odd to say things like 'p, but I am not absolutely certain that p'. In this paper, I aim to solve this conundrum. I suggest a pretense theory of assertion, according to which assertions of p are proposals to act as if the conversational participants were absolutely certain of p. I suggest that this explains why absolute certainty is not required to make assertions, while it is still problematic to voice your uncertainties once you have made an assertion. By voicing your uncertainties, you thwart your very own proposal to act as if everybody was absolutely certain.
CRIS-Team WoS Importer:2023-04-07